Fungal trunk pathogens associated with table grape decline in Northeastern Brazil - Kamila CORREIA; Marcos Paz CÂMARA; Maria Angelica BARBOSA; Rui SALES Jr.; Carlos AGUSTÍ-BRISACH; David GRAMAJE; Maela LEÓN; José GARCÍA-JIMÉNEZ; Paloma ABAD-CAMPOS; Josep ARMENGOL; Sami Jorge MICHEREFF (Phytopathologia Mediterranea, 2012)
During the last five years a decline of table grape plants has been noticed in nurseries, young plantations and vineyards of the Northeastern region of Brazil, where the management systems for grapevine production are adapted to the specific environmental conditions of a tropical viticulture. Samples of table grape plants showing decline symptoms were obtained from grapevine nurseries, young plantations and vineyards located in the São Francisco, Assú and Siriji Valleys in 2010, and were subjected to fungal isolation. Grapevine trunk pathogens were identified using morphological and molecular methods. Species recovered included Botryosphaeria mamane, Campylocarpon fasciculare, C. pseudofasciculare, Lasiodiplodia crassipora, L. parva, L. pseudotheobromae, L. theobromae, Neofusicoccum parvum, Phaeoacremonium aleophilum, Pm. parasiticum and Phaeomoniella chlamydospora. They are all reported for the first time on grapevine in Brazil, with the exception of L. theobromae. Moreover, Botryosphaeria mamane, Lasiodiplodia parva and L. pseudotheobromae are reported for the first time on grapevine, and C. fasciculare is reported for the first time on the American continent.